2017
DOI: 10.1038/s41598-017-17123-5
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for spectroscopy of liquid-exfoliated 2D materials: emerging photoluminescence of N-methyl-2-pyrrolidone

Abstract: N-methyl-2-pyrrolidone (NMP) has been shown to be the most effective solvent for liquid phase exfoliation and dispersion of a range of 2D materials including graphene, molybdenum disulphide (MoS2) and black phosphorus. However, NMP is also known to be susceptible to sonochemical degradation during exfoliation. We report that this degradation gives rise to strong visible photoluminescence of NMP. Sonochemical modification is shown to influence exfoliation of layered materials in NMP and the optical absorbance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…Although NMP was extensively employed for exfoliating nanosheets, caution is advised since it is considerably unstable; it decomposes easily and quickly with time, light, air, and sonication, furnishing byproducts and impurities that interfere with MoS 2 . Such experimental issues frequently lead to wrong spectroscopic assignments when basic properties of exfoliated nanosheets are examined.…”
Section: Edge and In‐plane Covalent Functionalizationmentioning
confidence: 99%
“…Although NMP was extensively employed for exfoliating nanosheets, caution is advised since it is considerably unstable; it decomposes easily and quickly with time, light, air, and sonication, furnishing byproducts and impurities that interfere with MoS 2 . Such experimental issues frequently lead to wrong spectroscopic assignments when basic properties of exfoliated nanosheets are examined.…”
Section: Edge and In‐plane Covalent Functionalizationmentioning
confidence: 99%
“…The origin of this photoluminescence has been attributed to the sonochemical degradation of the NMP suffered during the preparation of the NFs. Previous investigations [67,68] have demonstrated that sonication of pure NMP produces contaminating organic nanoparticles. Ogilvie et al [68] also reported strong photoluminescence and enhancement of the optical absorbance of NMP-based NFs after a sonication treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of the nitrogen-doped graphene–C 60 nanoensemble, N-G/C 60 4 , was performed by N -alkylation of pyrrole-type nitrogen atoms onto the graphene surface using potassium carbonate (K 2 CO 3 ) as the base ( Scheme 2 ). 12 For this purpose, commercial nitrogen-doped graphene (; ), N-G, was initially exfoliated in N -methyl-2-pyrrolidone (NMP) 20 for 15 hours in a sonication bath (37 kHz) at constant temperature (25 °C). The sample was then centrifuged at an appropriate speed to remove the non-exfoliated nitrogen-doped graphene and heavier layers to give predominantly a dispersion of few-layer graphene sheets (3–4 layers) (see further details in the AFM section and ESI † ).…”
Section: Resultsmentioning
confidence: 99%